Intermittent Exotropia and Overminus Lens Therapy in Macedonia - Ljubic, Antonela; Dimitrova, Galina; Zechevikj, Snezana; Trajkovski, Vladimir (Sciendo, 2024)
AIM: Intermittent exotropia (IXT) is the most common form of exodeviations. The aim of our study was to investigate the outcome after overminus lens therapy in children and young adults with IXT. METHODS: Fifty-three children and young adults with IXT, aged 3–33 years, from Macedonia, underwent slit-lamp examination, ocular motility, and refraction. For assessing near control in children and young adults with IXT, we used an office-based Mayo Scale. RESULTS: Most of the patients had Mayo score 1 (30.2%) and Mayo score 2 (26.4%). A Mayo score of 3 was presented in 18.9% of the patients, and Mayo score of 0 in 15.1%. A Mayo score of 4 was presented in 5.7%, and Mayo scored only in 3.8% of the IXT patients. After prescribing overminus glasses, 43.4% of the IXT patients showed better outcomes with better punctum proximum convergence and/or, better stereoacuity, and/or smaller near angle of deviation (in pdp). 52.8% same motility and sensory outcome was observed, whereas only in 3.8% worse findings were reported. CONCLUSIONS: Our study group was with a mean age over 5 (10.2 years) and we used lower overminus therapy (add. −0.75 D). The following studies of overminus lens therapy on IXT children and young adults over 5 years of age, should confirm our findings of a high percentage of improvement in terms of Mayo near control assessment.
Keywords: Exotropia; Intermittent exotropia; Overminus lens therapy; Office based control score (Mayo)